Family Expectation and Poverty Alleviation Program: Approaches to Family Development Laws, Sustainable Development Goals, and Maqashid Sharia - Lilis Hidayati Yuli Astutik; Iffatin Nur; Mashuri Mashuri (Justicia Islamica, 2022)
This research intends to evaluate the Family Expectation Program to alleviate poverty through the lens of Population and Family Development Laws, Sustainable Development Goals, and Maqashid al-Sharia. Poverty becomes a problem in human life and affects individual and social lives. This condition has made the United Nations initiate the Sustainable Development Goals (SDGs) program, which among others, aims to alleviate poverty worldwide. As a member country of the United Nations, Indonesia welcomes this initiative by preparing several national poverty alleviation programs, including Program Keluarga Harapan (PKH)/ Conditional Cash Transfer Program. This study used a qualitative research approach with a case study and multi-site design to evaluate this program. Through the study locus in Tulungagung and Trenggalek Regencies, East Java, the results of this study indicate that the PKH program in the two locations is following the objectives of Islamic law, including the protection of religion (hifz al- din), the protection of human soul and body (hifz al-nafs), the protection of wealth (hifz al-mal), the protection of mind (intelligence) (hifz al-'aql), the protection of lineage (hifz al-nasl), and the protection of honor (hifz al-'ird¸). The results of this research hopefully contribute to setting up poverty alleviation-based -government policies through family development programs to pursue Sustainable Development Goals (SDGs) based on the values of Maqashid al-Sharia.